MOTOR SKILLS TRAINING - A BASIC FACTOR IN TRAINING JUNIOR FOOTBALLERS - Tatarcan Catalin-Andrei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
One of the basic factors in the sports training of footballers at all levels, including junior level, is motor skills training. Specifically, the junior age coincides, to a large extent, with the sensitive periods of development of most motor skills, which is why this age should be given greater attention by football specialists. Thus, in order to start the differentiated development of specific motor skills at junior level in the game of football, it is necessary to experimentally assess the level of their development for each skill. These data are necessary to be compared with the national standards of Romania for the given age. In this way it is possible to intervene with different modern methods in order to optimize the level of motor skills training of junior footballers.